Rethinking Our Classrooms: Teachers’ Perceptions on Integrating Transferable Skills in the Classrooms to Create an Active Learning Environment - Khabeishvili, Guranda (European Scientific Journal, ESJ, 2024)
Despite many efforts to promote transferable skills development, it remains a challenge for Higher Education Institutions (HEIs) and schools. To improve education practices and meet the challenges of an ever-changing environment, it is vital to introduce a paradigm shift in education. In light of this, it is significant to identify and implement the teaching strategies that facilitate transferable skills development. There has long been a controversy over the traditional pedagogical style of lecture delivery as opposed to an active learning environment in which learners are engaged in the learning process itself. The paper sheds light on various ways of integrating transferable skills in the classroom. It examines diverse methods, teaching/learning strategies, and educational tools that aim at promoting a learner-centered learning environment, to ensure the development of transferable skills, such as critical thinking, teamwork, communication, collaboration, creativity, research skills, etc. Creating such a learning environment stimulates students’ interests, engagement, and motivation. Consequently, it overviews a practical application of some activities and strategies that can activate the skills as well as reveals the results of findings that showed teachers’ perception regarding a practical application of some methods and strategies to enhance transferable skills. This research is significant by identifying the indicators of an active learning environment, which encourage educators to reimagine their classrooms and implement innovative teaching practices.